Pembuatan Design Halaman Perusahaan pada Ami Florist - Surya Tjahyadi; Rio Fernando (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Ami Florist, located in Batam City, Riau Islands, is a partner that focuses on selling flower board services, including imported and artificial flowers. Founded in 2016 under the leadership of Johan Sun, Ami Florist faced challenges in attracting customer interest for its flower board services. In his efforts to overcome this problem, Johan felt the need to have a company page that was effective in promoting his services to the wider community. In this community service project, we aim to help Ami Florist in designing and implementing an innovative company page design using 2D design methods and Adobe Photoshop 2020 application tools. With this new page design, we hope to increase public interest and awareness of flower board services offered by these partners, as well as supporting their business development positively.